Relevansi Psikologi Perkembangan Terhadap Strategi Pembelajaran Pendidikan Agama Islam Di Era Digital : Pendahuluan, Metode, Pemabahasan, Daftar Pustaka - Muhammad Sandi Azhar; Gan Nurbanani Yusuf; Zaenal Abidin (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
With the advancement of digital technology, there have been significant changes in approaches to Islamic religious education, particularly in terms of adapting the learning process to the characteristics of students in the digital generation. The purpose of this study is to examine the relationship between developmental psychology and approaches to Islamic religious education in the digital age. This study employs a qualitative method, specifically a literature review. Data were obtained by reviewing various scientific sources, including books and journals related to developmental psychology, student characteristics, and digital learning approaches for Islamic religious education. Data collection was also conducted through a review of documentation and analysis of scientific literature published over the past five years. The research results indicate that developmental psychology is crucial in determining adaptive, humanistic, and contextual Islamic religious education strategies that account for students’ cognitive, emotional, social, and moral development. When tailored to students’ psychological developmental needs, digital-based learning methods such as e-learning, interactive learning, blended learning, and project-based learning are considered capable of enhancing students’ motivation, engagement, and understanding. However, in the digital age, the integration of developmental psychology into Islamic religious education still faces many challenges. These include teachers who lack the skills to implement digital pedagogy, a shortage of technological resources, and the negative effects of digital media on student behavior. Therefore, methods of teaching Islamic religious education in the modern era must be designed innovatively, striking a balance between the use of technology and the reinforcement of Islamic values.